Abusive behavior of employees against their managers: an explorative study - Avisar, Galit; Cohen, Tami; Tziner, Aharon; Bar-Mor, Hadara (Frontiers in Psychology, 2025)
ObjectiveWorkplace abusive behavior is behavior that causes harm to people’s dignity and their mental and physical health. It encompasses abusive or violent behaviors, harassment, or intimidation, and can be directed against co-workers, managers, customers, or suppliers. Extant literature has focused mainly on abuse by managers, or by peers and colleagues. This study investigates ‘upward abusive behavior’“– abuse by an employee against people in management positions, and whether there is awareness of or exposure to this phenomenon. While not common, abusive behavior from employees toward their supervisors can manifest through disrespectful conduct and inappropriate challenges to authority, creating a difficult work environment.Method120 employees and managers from a variety of organizations, and with varying seniority, answered a questionnaire (based on Tepper, 2000) that included 15 statements relating to the conduct and dynamics between employees and managers. The statements were assessed on a Likert scale of 1 (“I cannot remember him/her ever using this behavior with me”) to 5 (“He/she uses this behavior very often with me”).ResultsSeveral significant associations were found between managers’ exposure to abuse and some of the respondents’ demographic data such as age, gender, seniority in the workplace, and tenure.ConclusionThe result of this exploratory study indicates that many employees and managers are aware of the existence and various aspects of upward abuse as it is expressed in organizations. However, they still do not give it an explicit name or are not willing to acknowledge it. The phenomenon of employee abuse of managers is not only not recognized in legislation (as is the phenomenon of regular workplace abusive behavior), but it is also not discussed in organizations. There are no procedures or processes to prevent and eradicate it.